The Effects of Service Quality and Service Marketing Mix on Customer Retention Towards Budget Hotels in Iraq The Mediating Role of Service Value - Othman, Bestoon; N. Mohamad Khan, Twana; Ahmad, Paiman (JBS Nexus, 2026)
Population growth in Iraq is now becoming a major concern in the Iraq, and in the case of a shortage of hotel rooms, this will affect the demand for luxury hotels as consumers will turn to budget hotels. The budget hotel indeed has a key role in economic sectors, the property market, and human life. Since the demand for budget hotels in the Iraq is very high, they should have excellent hotel facilities and therefore it provides a space to study the service quality and marketing mix offered by these budget hotels. Besides of examining the service value as a mediator in the relationship of these effects on retention. In addition, this paper incorporated a new dimension of service marketing mix, namely after-sale rather than the conventional 7P’s marketing service mix. The Stimulus-Organism-Response theory guided the theoretical structure of the analysis. Three of the four main variables, namely service quality, service marketing mix, and service value, were conceptualized and analyzed using the reflective-formative approach as a second-order construct. Customer retention as the dependent variable was assessed reflectively across four multiple items. Data was collected from 385 budget hotel clients residing in budget hotels in the Iraq and analyzed using SPSS and SmartPLS software. Findings indicated significant and direct relationships between service quality, service marketing mix, service value, and customer retention. It was also found that service value has a full mediation effect. This study will be of interest to the Hotel industry in understanding how service quality and service marketing mix strategies are essential for maintaining a long-term relationship with customers.